QUALITY OF LIFE IN PREGNANT WOMEN WITH CHRONIC SLOW TRANSIT CONSTIPATION - І. Лещишин; Л. Маркулан; П. Бик; Я. Сусак; Н. Мартинюк; О. Охоцька (Bukovynian State Medical University, 2024)
A signifi cant number of pregnant women suff er from constipation, which tends to worsen as pregnancy progresses. Chronic constipation worsens the course of pregnancy and may require emergency surgery with possible negative consequences for the fetus and the woman. The negative impact of constipation during pregnancy can be reduced by eliminating the manifestation of symptoms before it. The recommended surgical procedure is total colectomy. The aim of this study was to evaluate the quality of life (QoL) of pregnant women with chronic slow transit constipation (CSTC) after conservative versus surgical treatment. Method: Between 2017 and 2022, a comprehensive study was conducted on 46 women with CSTC that was resistant to conservative treatment. Among them, 22 patients underwent surgery (group M), while 24 patients received conservative treatment (group C). Quality of life was assessed using the SF-36 scale before treatment, 90 days after treatment initiation, and during each trimester of pregnancy. Rezalts: After treatment, physical QoL was comparable between groups (47.92±3.7 vs. 45.99±4.71), whereas mental QoL was signifi cantly higher in the surgical group (50.59±2.79 vs. 46.94±4.85, p=0.009). In the second trimester, the surgical group had signifi cantly higher physical QoL than the non-surgical group (43.9±2.4 vs. 40.5±2.6, p = 0.029). In the third trimester, both physical (39.3±3.6 vs. 29.7±5.1, p = 0.003) and mental (51.7±2.5 vs. 40.5±6.3, p = 0.003) QoL scores were signifi cantly higher in the surgical group. Conclusions: Compared with conservative therapy, colectomy improves the quality of life of pregnant women with CSTC, suggesting that it is a safe and eff ective treatment option before pregnancy.